The Teaching of English in Acceleration Class - Fransiskus Jonet Prihandoko (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
This study aims at describing the teaching process of English in acceleration class at SMUN 3 Malang in terms of teaching materials, media, and teaching techniques. This study is a descriptive qualitative research. The subject was the English teacher in acceleration class at SMUN 3 Malang. Findings shows that the teacher used three different English books and other source material such as English newspaper, pictures, posters, and some materials from the internet as the teaching materials. The teacher used some kinds of media in his teaching, such as: audio media, visual media, and audio-visual media. He used language lab for teaching listening program. For the teaching techniques, the teacher used some kinds of teaching techniques; they are; lecturing, games, simulation, and discussion techniques. Obviously, students speak all at once trying to accomplish their task, and this causes noise that may bother other colleagues. The qualifications of English teachers in acceleration class should be different with the qualification of English teachers in regular class. They also have to conduct a better entrance selection system for acceleration class students. The criteria that must be passed are not only IQ test score, interview, and academic score, but also creativity test score. Key words: acceleration class, teaching material and media, teaching technique